(untitled) (TAJ: Journal of Teachers Association, 2009)
Management of close comminuted fracture in the shaft of femur in adult is a difficult task. Here we report a case who was managed by open reduction and internal fixation with broad dynamic compression plate without stripping of Periosteum. doi: 10.3329/taj.v15i2.3919 TAJ December 2002; Vol.15(2): 96-97